2022
DOI: 10.21608/jenvbs.2022.170499.1197
|View full text |Cite
|
Sign up to set email alerts
|

Significant Use of Molasses and foliar application of Ca (NO3)2 on Improving of some Soil properties and yield of Rice under salt affected soils

Abstract: FIELD experiment was conducted at Kafr El-Sheikh Governorate, North Nile Delta area, Egypt during the two successive growing seasons 2020 and 2021 to assess the effect of different levels from molasses and foliar application of Ca (NO 3 ) 2 on some soil properties and yield of rice. Spilt-plot design was used, which the main plots were assigned to four treatments of molasses (i.e., M1: without molasses, M2:140 L ha -1 , M3: 280 L ha -1 , M4:420 L ha -1 ), while foliar application of Ca(NO 3 ) 2 treatments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Also Bd was significant decreased (P ≤ 0.05) and recorded lowest values (1.30 and 1.299) for 1st season and 2 nd season due to the interaction between V120 and CT+. These results were supported by (Jiang et al, 2012 andOmara et al, 2022).…”
Section: Soil Physical Propertiessupporting
confidence: 72%
See 1 more Smart Citation
“…Also Bd was significant decreased (P ≤ 0.05) and recorded lowest values (1.30 and 1.299) for 1st season and 2 nd season due to the interaction between V120 and CT+. These results were supported by (Jiang et al, 2012 andOmara et al, 2022).…”
Section: Soil Physical Propertiessupporting
confidence: 72%
“…It is composed to a large extent of water, organic matter and mineral elements. The results of such studies show that, when used correctly, vinasse contributes to the improvement of soil properties and agricultural productivity (Jiang et al, 2012;Omara et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in soil microbial activity due to the molasses application was also noted by Waguespack et al (2022). Furthermore, another study by Omara et al (2022) indicated that the addition of molasses incline dehydrogenase activity. In addition, the β-glucosidase activity increased as well by the presence of molasses (Yi et al, 2020).…”
Section: Introductionmentioning
confidence: 60%